Characterization of in-barn heat processed swine mortalities - Ramirez, Brett C.; Jeon, Ryan; Stender, Dave R.; Kohl, Kris D.; Rademacher, Chris J.; Brown, Justin T.; Mogler, Dwight (Frontiers in Veterinary Science, 2023)
In-barn heat processing of mass swine mortalities to inactivate pathogens could enable more carcass disposal options and reduce the risk of pathogen spread in the event of a foreign animal disease (FAD) outbreak. A 12.2 x 12.2 x 2.4 m (W x L x H) heat processing room was created using a temporary wall inside a de-commissioned commercial gestation barn in northwest Iowa. Eighteen swine carcasses (six per group) divided into three weight groups (mean ±SD initial carcass weights: 31.8 ±3.3, 102.7 ±8.1, and 226.3 ±27.6 kg) were randomly assigned a location inside the room. Three carcasses (per weight group) were placed directly on the concrete slats and on a raised platform. One carcass per weight group and placement (n=6) were instrumented with five temperature sensors were inserted into the brain, pleura, peritoneal, ham, and bone marrow of femur as well as a sensor attached directly to the skin surface. Environmental conditions (ambient and room) as well as carcass temperatures were collected at 15-min intervals. Carcasses were subjected to an average room temperature of 57.3°C ±1.2°C for 14 days. Average (±SD) reduction from initial weight for carcasses on slats was 45.0% ±4.70% (feeder), 33.0% ±8.30% (market) and 34.0% ±15.80% (sow), and carcasses on a raised platform was 39.0% ±6.80% (feeder), 49.0% ±11.30% (market), and 45.0% ±6.70% (sow). There was a significant interaction between carcass placement (slats and raised) and carcass weight loss for the market weight group. When average carcass surface temperature was at 40.6°C, 43.3°C, and 46.1°C (data grouped for analysis), the average internal carcass temperature for most measurement locations were significantly different across carcass weight groups and were significantly different between carcasses on a raised platform and on slats. This preliminary analysis of carcass weight loss and leachate production as well as the temperature variation in different sized carcasses can be used for planning and evaluating mass swine mortality management strategies.